Faktor - Faktor Pendorong dan Penghambat Graduasi Sejahtera Mandiri Penerima Program Keluarga Harapan di Kabupaten Lampung Tengah - S., Lilis Suryati; Rangga, Kordiyana K.; Indriyani, Yaktiworo; Sayekti, Wuryaningsih Dwi; Syarief, Yuniar Aviati (Fakultas Pertanian, Universitas Lampung, 2023)
ABSTRACT Based on observations in 2019, PKH beneficiaries Families were faound who are already socially capable, but are not willing to graduate independently, even though PKH social assistants have already carried out the educational process. Such a situation really needs proper management/strategy because if left unchecked it will cause various problems. This research was conducted in September 2022 - February 2023 with 12 PKH social assistants and 6 PKH KPM informants in Central Lampung Regency. Methods of data analysis using qualitative analysis. The results of the study stated that factors success of independent prosperous graduation in Central Lampung, namely early competence PKH social assistants, motivation of the PKH District coordinator, behavior innovative human resources and KPM PKH, appreciation from the Indonesian Ministry of Social Affairs to assistants PKH’s social achievements, KPM’s visionary mindset, high fighting power from KPM, the ability KPM tu manage family finances, self awareness and shame within KPM that encourages KPM to apply for graduation from PKH, sensitivity KPM social and self confidence, support from the KPM family, KPM craft attend Family Capacity Building Meetings, support from village officials and subdistrict. Factors that become obstacles to the prosperous graduation is defference in PKH HRD perceptions about graduation prosperous independence, low self efficacy of most PKH social assistants, there is no support from the village apparatus, the standard criteria for poor families the relevant corals are used, the independent prosperous graduation data still comes out as PKH beneficiaries, and recertification instruments are not implemented.